THE JUDGE'S CONSIDERATIONS IN IMPROVING SENTENCE AGAINST THE DEFENDANT WHO COMMITTED A CRIME OF CORRUPTION IN THE VILLAGE BRAJA GEMILANG, EAST LAMPUNG DISTRICT (STUDY DECISION NUMBER 14/PID.SUS TPK/2022/PN TJK) - Nyimas Maharani Putri Pertiwi; Muhtadi Muhtadi; HS Tisnanta (Jurnal Ilmiah Advokasi, 2023)
Corruption often occurs in Indonesian society. In terms of the amount of state financial losses, the number of cases, the scope that has penetrated every aspect of society's life, and the aspect of criminal acts that are carried out more methodically, developments continue to increase from year to year. The increase in uncontrolled corruption cases has the potential to be a disaster for the state, nation as well as the economy.This journal research is based on two problems, namely how the defendant recovers state losses caused by corruption committed by the Village Head and also how the judge considers when handing down a decision against the defendant for a criminal act of corruption committed by the Head of Braja Gemilang Village, East Lampung Regency (Decision Study Number 14/Pid.Sus TPK/2022/PN Tjk). Based on data obtained from a news portal, Firli Bahuri as Chair of the Corruption Eradication Commission (KPK) said that from 2012 to 2021, as many as 686 village heads were involved in village fund corruption in 601 cases. The high number of corruption cases committed by village heads is considered urgent considering the large number of APBD funds that are not allocated properly. The purpose of conducting this research is so that readers know, understand and analyze how judges can impose sentences on village heads who commit criminal acts of corruption and also so that readers can find out how defendants of criminal acts of corruption recover state losses in criminal acts of corruption.Keywords: Corruption, Village Head, Judge's Consideration